Stanislaw Chojnacki: Ethiopian Icons. Catalogue of the Collection of the Institute of Ethiopian Studies Addis Ababa University (Aethiopica, 2001)
Review
Keywords: History; Art; Handicrafts; Iconography; Institute of Ethiopian Studies; Museum